Ndufc2 Gene Inhibition Is Associated With Mitochondrial Dysfunction and Increased Stroke Susceptibility in an Animal Model of Complex Human Disease. Issue 2 (17th February 2016) - Rubattu, Speranza; Di Castro, Sara; Schulz, Herbert; Geurts, Aron M.; Cotugno, Maria; Bianchi, Franca; Maatz, Henrike; Hummel, Oliver; Falak, Samreen; Stanzione, Rosita; Marchitti, Simona; Scarpino, Stefania; et al.
Abstract : Background: The genetic basis of stroke susceptibility remains to be elucidated. STR1 quantitative trait locus (STR1/QTL) was identified on rat chromosome 1 of stroke‐prone spontaneously hypertensive rat (SHRSP) upon Japanese‐style stroke‐permissive diet (JD), and it contributes to 20% of the stroke phenotype variance. Methods and Results: Nine hundred eighty‐six probe sets mapping on STR1 were selected from the Rat RAE230A array and screened through a microarray differential expression analysis in brains of SHRSP and stroke‐resistant SHR (SHRSR) fed with either regular diet or JD. The gene encoding Ndufc2 (NADH dehydrogenase [ubiquinone] 1 subunit), mapping 8 Mb apart from STR1/QTL Lod score peak, was found significantly down‐regulated under JD in SHRSP compared to SHRSR. Ndufc2 disruption altered complex I assembly and activity, reduced mitochondrial membrane potential and ATP levels, and increased reactive oxygen species production and inflammation both in vitro and in vivo. SHRSR carrying heterozygous Ndufc2 deletion showed renal abnormalities and stroke occurrence under JD, similarly to SHRSP. In humans, T allele variant at NDUFC2/rs11237379 was associated with significant reduction in gene expression and with increased occurrence of early‐onset ischemic stroke by recessive mode of transmission (odds ratio [OR], 1.39; CI, 1.07–1.80; P =0.012). Subjects carrying TT/rs11237379 and A allele variant at NDUFC2/rs641836 had further increased risk of stroke (OR=1.56; CI, 1.14–2.13; P =0.006). Conclusions: A significant reduction of Ndufc2 expression causes complex I dysfunction and contributes to stroke susceptibility in SHRSP. Moreover, our current evidence may suggest that Ndufc2 can contribute to an increased occurrence of early‐onset ischemic stroke in humans.